Image-based deep learning reveals the responses of human motor neurons to stress and VCP-related ALS - Patani, Rickie; Luisier, Raphaelle (University of Dundee, 2021)
The aim of the study was to investigate relationships between ALS-related RNA-binding proteins and ALS, under different stress conditions.
Keywords: FOS: Biological sciences